2020
DOI: 10.1002/er.5113
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen absorption/desorption properties of light metal hydroxide systems

Abstract: Summary In light metal hydroxide systems, hydrogen desorption generally occurs in exothermic reactions; therefore, these reactions are irreversible in principle. However, according to theoretical calculation of thermodynamics, some of these systems can desorb hydrogen in endothermic reactions. In this research, several hydroxide systems were studied to clarify the reversibility of these systems. Six types of hydroxide systems (XH + Y(OH)n, X: Li, Na, Y: Li, Na, Mg) were prepared by ball‐milling, then the desor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Several researches in this area are focused on metal hydrides, metal organic frameworks and carbon materials while these materials are suffered from slow kinetics, inappropriate thermodynamics and low efficiencies 43 . Organic polymers, due to the structural flexibility, thermomechanical, and physicochemical properties, are recently developed as the host for hydrogen sorption in the electrochemical systems 44 . The physisorption of hydrogen is a reversible process with continuous adsorption and desorption profiles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researches in this area are focused on metal hydrides, metal organic frameworks and carbon materials while these materials are suffered from slow kinetics, inappropriate thermodynamics and low efficiencies 43 . Organic polymers, due to the structural flexibility, thermomechanical, and physicochemical properties, are recently developed as the host for hydrogen sorption in the electrochemical systems 44 . The physisorption of hydrogen is a reversible process with continuous adsorption and desorption profiles.…”
Section: Resultsmentioning
confidence: 99%
“…43 Organic polymers, due to the structural flexibility, thermomechanical, and physicochemical properties, are recently developed as the host for hydrogen sorption in the electrochemical systems. 44 The physisorption of hydrogen is a reversible process with continuous adsorption and desorption profiles. Since the hydrogen density is low, almost weak interactions occur between hydrogen and solid materials.…”
Section: Electrochemical Properties and Hydrogen Storage Performancementioning
confidence: 99%
“…MgH 2 ‐LiBH 4 system desorbs hydrogen as follows: 2LiBH4+MgH22LiH+MgB2+4H2. LiH‐LiNH 2 system absorbs and desorbs hydrogen as follows 8 : LiH+LiNH2Li2NH+H2 5.20.25emwt%H2,italicΔH=44.50.25emkJ/molH2. Also, Li‐Mg‐N‐H system has low value of enthalpy change and lower temperature of around 180°C for hydrogen absorption/desorption. The overall reaction of Li‐Mg‐N‐H system is described as follows 5 : MgNH22+2LiHLi2MgN2H2+2H2 5.50.25emwt%H2,italicΔH=44.30.25emkJ/molH2. So far, a lot of research on complex hydrides has been reported; however, the research on hydroxides has not been reported very much 6,9,10 . In this study, we focused on the hydride hydroxide systems, because we expected that promising hydrogen storage material would be developed from hydride hydroxide systems.…”
Section: Introductionmentioning
confidence: 99%
“…LiOH desorbs H 2 O by thermal decomposition. On the other hand, LiH‐LiOH system desorbs H 2 as follows 10 : 2LiOHLi2normalO+H2normalO LiH+LiOHLi2normalO+H2 6.270.25emwt%H2,italicΔH=22.50.25emkJ/molH2. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation